2020
DOI: 10.21203/rs.3.rs-59508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world Efficacy and Safety of Dulaglutide in Korean Patients with Type 2 Diabetes Mellitus: A Retrospective Study in a Tertiary Referral Center

Abstract: Background: This study was conducted to evaluate the efficacy and safety of once-weekly dulaglutide therapy as add-on to oral antidiabetic drugs (OADs) and basal insulin in Korean patients with type 2 diabetes mellitus (T2DM) in the real-world clinical practice.Methods: We retrospectively reviewed the medical records of 112 patients who received dulaglutide in a tertiary referral center. The primary efficacy endpoint was a change in glycated hemoglobin (HbA1c) between baseline and 6 months. The secondary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…A recent literature review investigating the real-world effectiveness of Dulaglutide reported a 0.5-2.2% reduction from baseline in HbA1c after 3 to 24 months across a number of 20 studies [19]. Two recent retrospective studies found a reduction of −1.13% [20] and −0.97% [23] in HbA1c after 6 months of Dulaglutide initiation. Different changes in HbA1c reported in these studies could be related to previous antihyperglycemic regimens associated with Dulaglutide, duration of diabetes, duration of follow-up, and factors such as lower treatment compliance and adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent literature review investigating the real-world effectiveness of Dulaglutide reported a 0.5-2.2% reduction from baseline in HbA1c after 3 to 24 months across a number of 20 studies [19]. Two recent retrospective studies found a reduction of −1.13% [20] and −0.97% [23] in HbA1c after 6 months of Dulaglutide initiation. Different changes in HbA1c reported in these studies could be related to previous antihyperglycemic regimens associated with Dulaglutide, duration of diabetes, duration of follow-up, and factors such as lower treatment compliance and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In real-world settings, bodyweight was reduced by 2.1 to 6.4 kg across a number of 15 real-world studies including patients treated with Dulaglutide followed over periods ranging from 3 to 12 months [19]. Also, two retrospective clinical studies reported a significant reduction of −2.9 kg [20] and −2.05 kg [23] in bodyweight after 6 months of Dulaglutide treatment. Different outcomes in terms of bodyweight changes could be explained by the different previous treatments used by patients when Dulaglutide was initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation